ENHANCING TUBERCULOSIS CASE FINDING THROUGH SULI SIMULATOR APP: A CASE STUDY IN LUBUKLINGGAU CITY, SOUTH SUMATERA PROVINCE, INDONESIA - Kurniawan, Depit; Syakurah, Rizma Adlia (The Indonesian Journal of Public Health, 2024)
Introduction: Tuberculosis (TB) remains a significant public health challenge and is included as one of the targets in the Sustainable Development Goals (SDGs). TB case finding in Lubuklinggau City decreased from 967 in 2019 to 273 (24,37%) in 2020. Aims: This study aims to analyze the TB disease management program strategy implementation in contact investigation activities by utilizing the SULI SIMULATOR application. Method: A qualitative design with a participatory action research (PAR) approach was employed, involving focus group discussions, in-depth interviews with 36 informants, and document review. Data were validated using triangulation methods and sources, followed by thematic analysis. Result: The findings revealed that, in terms of input, some PHC lacked analysts in their human resources. In terms of process, the successful implementation of the TB disease prevention program, with the application of SULI SIMULATOR for TB contact investigation, led to an increase in the case detection rate (CDR) to 255 cases (22.76%) in 2021 compared to the previous year's 237 patients (21.16%). Conclusion: The active involvement of the community and family is crucial in promoting early detection of TB cases through contact investigation activities, as well as providing support for treatment in family and community-based health efforts